The total work measured during a high intensity isokinetic fatigue test is associated with anaerobic work capacity - Bosquet, L.; Gouadec, K.; Berryman, N.; Duclos, C.; Gremeaux, V.; Croisier, J. L. (Journal of Sports Science & Medicine, 2016)
The purpose of the study was to determine whether total work measured during a high intensity isokinetic fatigue test (TWFAT) could be considered as a valid measure of anaerobic work capacity (AWC), such as determined by total work measured during a Wingate Anaerobic Test (TWWAnT). Twenty well-trained cyclists performed 2 randomly ordered sessions involving a high intensity isokinetic fatigue test consisting in 30 reciprocal maximal concentric contractions of knee flexors and extensors at 180°·s-1, and a Wingate Anaerobic Test. We found that TWFAT of knee extensors was largely lower than TWWAnT (4151 ± 691 vs 22313 ± 2901 J, respectively, p < 0.05, Hedge`s g = 4.27). Both measures were highly associated (r = 0.83), and the 95% limits of agreement (LoA) represented 24.5% of TWWAnT. TWFAT of knee flexors (2151 ± 540 J) was largely lower than TWWAnT (p < 0.05, g = 9.52). By contrast, both measures were not associated (r = 0.09), and the 95% LoA represented 31.1% of TWWAnT. Combining TWFAT of knee flexors and knee extensors into a single measure (6302 ± 818 J) did not changed neither improved these observations. We still found a large difference with TWWAnT (p < 0.05, g = 5.26), a moderate association (r = 0.65) and 95% LoA representing 25.5% of TWWAnT. We concluded that TWFAT of knee extensors could be considered as a valid measure of AWC, since both measure were highly associated. However, the mean difference between both measures and their 95% LoA were too large to warrant interchangeability.